Adverse Events With Sustained-Release Donepezil in Alzheimer Disease: Relation to Body Mass Index. Issue 4 (August 2017) - Lee, Chunsoo; Lee, Kyungsang; Yu, Hyewon; Ryu, Seung-Ho; Moon, Seok Woo; Han, Changsu; Lee, Jun-Young; Lee, Young Min; Kim, Shin-Gyeom; Kim, Ki Woong; Lee, Dong Woo; Kim, Seong Yoon; et al.
Abstract: Purpose/Background: Sustained-release, high-dose (23 mg/d) donepezil has been approved for treatment of moderate to severe Alzheimer disease (AD). Based on a previous clinical trial, body weight of less than 55 kg is a risk factor for adverse events with donepezil 23 mg/d treatment in global population. Methods/Procedures: To clarify whether this finding is consistent across ethnic groups that vary in absolute body mass, we recruited Korean patients aged 45 to 90 years with moderate to severe AD who had been receiving standard donepezil immediate release 10 mg/d for at least 3 months. After screening, we analyzed a final cohort of 166 patients who received donepezil 23 mg/d for 24 weeks to compare the occurrence of treatment-emergent adverse events (TEAEs) between patients with high versus low body mass index (BMI) based on the World Health Organization overweight criteria for Asian populations (23 kg/m 2 ). Findings/Results: Treatment-emergent adverse events were reported by 79.45% of patients in the lower BMI group and 58.06% of patients in the higher BMI group (odds ratio, 2.79; 95% confidence interval, 1.39–5.63; χ 2 = 7.58, P = 0.006). In a multivariable survival analysis, the group with lower BMI showed a higher occurrence of TEAEs (hazard ratio, 1.83; 95% confidence interval, 1.25–2.68; P = 0.002). Implications/Conclusions: In Korean patients with moderate to severe AD receiving high-dose donepezil over 24 weeks, TEAEs were significantly more common in those with lower BMI (not clinically overweight), especially nausea. This finding may inform clinical practice for Asian patients.